Advances in big data : proceedings of the 2nd INNS Conference on Big Data, October 23-25, 2016, Thessaloniki, Greece /: proceedings of the 2nd INNS Conference on Big Data, October 23-25, 2016, Thessaloniki, Greece. ([2017]) - Unknown
No abstract available